A deixis study on the songs of Hillsong Worship in the Cornerstone (live) album - Emmanuella Laurensia Gabrielle Ondang; Suatmo Pantja Putra (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2023)
This study aims to determine deixis in the song lyrics and explain the meaning of deixis in theÂ Cornerstone (Live)Â album songs. TheÂ Cornerstone (Live)Â album by Hillsong Worship has thirteen songs and, in this study, four songs which are â€œCornerstoneâ€, â€œGreater Than Allâ€, â€œBeneath the Waters (I Will Rise)â€, and â€œEndless Lightâ€ will be discussed. The listeners might find difficulties understanding the meaning of song lyrics. That is why the researchers interprets the meaning of song lyrics through deixis. The result revealed that â€œCornerstone and Beneath the Waters (I Will Rise)â€ have five types of deixis namely person deixis time, deixis, place deixis discourse deixis, and social deixis. Meanwhile, â€œGreater Than Allâ€ and â€œEndless Lightâ€ only have four types of deixis. In addition, â€œGreater Than Allâ€ does not have place deixis and â€œEndless Lightâ€ does not have discourse deixis. Person deixis, time deixis, and social deixis are the types of deixis always existed in every song. Person deixis such as my, I, he and you is used to refer the speaker as subject and second person as well as third person is used to refer the object of the speaker.Â Â Time deixis such as now indicate the present time when the utterance happens. Place deixis such as come and at the cross give the location where the story of song happens. Discourse deixis such as and used to connect the previous and latest discourse. Social deixis like God is indicates the social status or relationship between the speaker and the object of the speaker.